PENGARUH PELAKSANAAN PROGRAM PELATIHAN DAN PENGEMBANGAN TERHADAP KINERJA PEGAWAI PT TERMINAL TELUK LAMONG - Santoso, Fidelio Bintang; Hariyana, Nanik; Puspita Sari, Magdalena Dini Wahyu (Gapenas Publisher, 2025)
This research aims to analyze the influence of training and development programs on employee performance at PT Terminal Teluk Lamong. The implementation of training and development programs is proven through hypothesis testing to have a significant influence on employee performance at PT Terminal Teluk Lamong. The percentage of influence generated by the training and development implementation variables on employee performance at PT Terminal Teluk Lamong amounts to 34,65%. Through this study, it is revealed that the implementation of training and development programs brings positive impacts on employee performance.